(untitled) (Al-Qamar, 2018)
In the modern theoretical and empirical research era the theory of al-Naẓm Abd al-Qāhir al-Jurjānī became the central idea for all modern critics and linguistics. They started finding out similarities between the theory of Abd al-Qāhir and the Swiss linguist Saussure’s theory of deconstruction and on the other hand similarities between Noam Chomsky and Abd al-Qāhir. All the research, had been done and yet has been doing by the academics and pioneer Arab and Non-Arab linguists, is surrounded by the theory of al-Naẓm. Abd al-Qāhir brought this theory to discourse the aʻjāz of Quran. He proved that Qur’ānic aʻjāz initially stands for several things that depict the beauty of Qur’ānic verses. The said research is answering following points: What al-Naẓm stands for? What is the role of al-Naẓm in illustrating Qur’ānic aʻjāz? How much the theory of al-Naẓm applicable to the Holy Texts?